Lobbying as Economic Statecraft: Regulatory Capture, Industrial Strategy, and the Reform of Influence Networks (Global Journal of Human-Social Science, 2025)
This study reinterprets corporate lobbying as a structural component of economic statecraft arguing that its role extends beyond corporate advocacy to shaping national industrial strategy and geopolitical competitiveness Drawing on Trevor Dryer s case study of federal lobbying in the financial sector alongside analyses of the CHIPS Act pharmaceutical regulation and firearm legislation in Massachusetts the study demonstrates how lobbying functions as a dual mechanism stabilizing regulatory environments for firms while advancing or undermining national economic sovereignty By integrating Post-Keynesian economic theory regulatory capture frameworks and gametheoretic models the paper reveals systemic vulnerabilities in the US lobbying regime It concludes with actionable legislative reforms designed to align lobbying with public interest goals such as cooling-off periods for officials industrial impact assessments and coalitional arbitrage strategies The findings challenge conventional distinctions between private interest advocacy and public economic strategy repositioning it as a pivotal arena for reasserting affirmative control over economic policy
Keywords: lobbying; regulatory capture; economic statecraft; industrial policy; legislative reform